The state of the property market in the Kingdom of Eswatini: trends since independence - Magagula, Bongani (Department of Construction Economics and Management, 2025)
Eswatini has for the longest of time been predominantly rural and people depended on subsistence farming for their livelihood. The increased rate of urbanisation can be viewed as a disruption to the rural lives of the people. Urbanisation has given birth to new cultures where people, especially those living in the peri-urban areas are now selling land meant for other uses such as farming and grazing. This is done without due consideration for the protection of crop fields, animal grazing land and water sources. The study seeks to establish an effective pathway to facilitating sustainable urban growth in eSwatini through the strengthening of rural-urban linkages in the country. In achieving the foregoing, firstly, one had to identify theory or literature on similar studies done elsewhere where the loss of rural/farmland because of indiscriminate urbanisation, its impact on people's livelihood and how such challenges are being addressed with emphasis on Sub-Saharan Africa. The theory was put into context by reviewing what is being done by the Eswatini Government to ensure the sustainability of the relationship between urban growth and rural/farmland activities which is meant to provide food security to urban land while reciprocal services are provided to rural/farmland. The literature review revealed that indeed, the negative effects of urban growth are not isolated only to Eswatini, but it does appear that other countries such as the USA and China did experience similar challenges during their early development stages. It was further discovered that urbanisation and agricultural land uses are always in competition with each other as they both thrive in similar land parcels in terms of terrain, and proximity to resources such as water. It is unfortunate for rural/farmland that it always loses against urbanisation in the absence of regulation. It is in that vein that the developed world has already put in place policies to guarantee a sustainable relationship between urban and rural linkages to manage the negative effects of urban growth. This has contributed greatly to ensuring food security and sustainable development. The research method employed is qualitative using non-probability sampling method and the research philosophy chosen is “Interpretivism” with the research approach being “Inductive Approach”. The research strategy is a single case study. Semi-structured interviews were undertaken with twelve of stakeholders involved in public service dealing with land issues The interview data was analysed using thematic analysis. The study concluded that Eswatini, currently has no policies governing the different uses of land in the country due to lack of political will where highly fertile land parcels are lost due to the destructive nature of urbanisation.